Efeitos da inclusão de leveduras autolisadas na terminação de novilhos confinados - Pontarolo, Giovanna Bobato (2021)
The use of functional additives such as self-smoothing yeasts has grown in the search for a product that provides greater performance and animal health, coupled with this favors the production of safe food for human consumption. The objective was to evaluate the productive performance, the ingestive behavior, the apparent digestibility of the feed and the carcass characteristics of steers finished in confinement under the effect of the inclusion of autolyzed yeasts in the diet: Treatment 1 - diet without yeast; Treatment 2 - diet with yeast (4 g animal day-1) and Treatment 3 - diet with yeast (7 g animal day-1). The product used is a functional ingredient obtained by the presence of yeast Saccharomyces cerevisiae autolyzed. The experimental design was entirely randomized, consisting of three treatments and six repetitions, where each repetition was represented by a bay with two animals. We used 36 whole bullocks, ½ Angus Nelore blood, from the same flock, with an average age of 11 months and initial mean live weight of 330 kg. The use of autolyzed yeasts promoted greater (P<0,05) daily live weight gain to the group that received 4 g animal day-1 (1,667 kg day-1) and better transformation capacity of the ingested MS into weight gain (5,58 kg of ingested MS daily weight gain-1) in the initial phase of confinement, in a simplified way this group showed a productive increase of 14.8% in the adaptation period. The apparent digestibility of diets containing autolyzed yeast was higher (P<0,05) than the control diet (73,96, 74,02 and 73,11 %, respectively), and its use did not interfere (P>0,05) in the ingestive behavior of the animals. It can be concluded that supplementation with autolysed yeasts at the inclusion level of 4 g day-1 promoted the best set of results in the termination of confined steers, and that the supplemented groups achieved the same degree of carcass finish.